A Piece of the Puzzle: Women and the Law as Viewed from the Late Medieval Court of Chancery. (October 2019) - Beattie, Cordelia
Abstract: This article uses fifteenth-century Chancery court bills to demonstrate how women negotiated solutions to social and legal disputes not just in Chancery but through a variety of legal jurisdictions. This approach sheds light on women's actions in courts where the records have not survived, and it also adds nuance to the long-running debate about whether equity was a more favorable jurisdiction for women than the common law. By bringing into view other jurisdictions—such as manorial, borough, and ecclesiastical ones—it demonstrates how litigants might pursue justice in a number of arenas, consecutively or concurrently. Some women approached Chancery because they did not think they would get justice in a lower court, while others were keen that their cases be sent back down so that they could be fully recompensed for the offences against them. A fuller understanding of the disputes to which Chancery bills refer complicates our understanding of why women "chose" Chancery. Chancery is only one piece of the puzzle of how women negotiated justice in late medieval England, but its records can also shed light on some of the missing pieces.